Предмет: Алгебра,
автор: gilemkhanova201
упростите выражение 3(х-2у)-2(3х-у)
Ответы
Автор ответа:
0
3(x-2y)-2(3x-y)=3x-6y-6x+2y=-3x-4y.
Автор ответа:
0
3x - 6y - 6x + 2y = 3x - 6x - 6y + 2y = - 3x - 4y
Автор ответа:
0
спасибо
Автор ответа:
0
упростите выражение (2а-3в)(а+в)-(а-2в)(а-в)
Похожие вопросы
Предмет: Английский язык,
автор: olaavorska609
Предмет: Английский язык,
автор: angeldemon5
Предмет: Английский язык,
автор: 928282933
Предмет: Математика,
автор: nika20069
Предмет: Математика,
автор: Акбалауса